EFFECTIVE TOOLS FOR INTEGRATING SOCIAL SERVICE RECIPIENTS INTO THE COMMUNITY - Barkasi, D. (Україна. Здоров’я нації, 2023)
The Slovak Republic is really actively responding to the changing situation in Europe regarding social issues, which can be seen at the changing legislation to the coordination of various activities at the regional level. The quality and level of social services in the Slovak Republic represents the state and self-government. The maturity of society is also measured by how it takes care of the weakest. The deinstitutionalisation of social service facilities leads to a certain extent to an increase in the quality of social service provision.